Detection of pathogens in swimming pools - Loh, Ying Ru (2015)
Waterborne outbreaks in swimming pools are persistent problems in the developed world. Although pools in Singapore have been reported to be free of Escherichia coli, no article was published to study and determine the microbes and potential pathogens that could be present in the water. In this study, backwash effluent of a swimming pool was collected to study the presence of antibiotic resistant microbial community. Potential bacterial pathogens were identified using two approaches that would complement each other: culture independent and culture dependent. Bacterial genomes and large plasmids were extracted for sequencing in culture independent approach whereas for culture dependent approach, plating was conducted on antibiotic medium to culture the antibiotic resistant bacteria. Based on the culture dependent approach, Bacillus and Aeromonas were discovered to be the most abundant in the pool backwash effluent. Furthermore, there were various nosocomial bacteria like Chryseobacterium spp, Flavobacterium spp, and Stenotrophomonas maltophilia and novel bacteria like Algoriphagus shivajiensis and Elizabethkingia anopheles being isolated. The common causative agents which contaminate aquatic environments are gram-negative bacteria. Hence, these findings imply the presence of antibiotic – resistance microbes which are potential pathogen to human in the pool and a need for constant surveillance to prevent waterborne outbreaks.